Ecstatic Encounters Bahian Candomblé and the Quest for the Really Real - van de Port, Mattijs (Amsterdam University Press, 2011)
For over a hundred years, writers, artists, anthropologists and tourists have travelled to Bahia, Brazil, in search of the spirit possession cult called Candomblé. Thus, successive generations of cultists have seen a long, steady stream of curious outsiders coming to their temples with notebooks and cameras, questions and inquisitive gazes, or ogling eyes and the hope of inclusion. This study asks what seduced these outsiders to seek access to the Afro-Brazilian religious universe and, conversely, how did cultists respond to the overwhelming interest in their creed and to becoming an object of the outsiders' imaginations. "Thriving in the gap between the sensuous fullness of life and the impossibility of its cultural representation, Ecstatic Encounters opens mind-blowing vistas for 'writing culture' in anthropology today."- Birgit Meyer, Free University of Amsterdam.